(untitled) (Revista horizonte, 2022)
Introduction: The purpose of this study was to determine the relationships between motor development and academic performance in 9- and 10-year-old schoolchildren from a subsidized private school in the commune of Puerto Montt. Material and methods: 45 schoolchildren (19 girls and 26 boys) were evaluated, based on a non-probabilistic sampling. The Test of Gross Motor Development TGMD-2 was used, which has been validated in the Chilean population. Results: No statistically significant associations were found between the academic performance of children in Language and Mathematics subjects with the level of Motor development. Conclusions: We do not find significant relationships between the level of gross motor development and academic performance, we presume that it may be because of the low motor development of the evaluated.